(3GdahGFO GdSQjI aj TQM GdLRQjIs - (3QVj GdOjf eMeO Hf EHQGgje GdMdHj GdeYQha HGHf GdMfHdjs
(3ChdgG (B:s
(3CeG HYO ajbhd abjQ dWa Gddg GdMfaj , eMeO GdfGOaj GdMdHj GdMfaj, efMg Gddg JYGdi s
(3BNQgG (B:s
(3dcf dGjNai Cf gPG GdHjJ eY eJdhjg NGQL Yf GdebOeI HbQjfI bhdg aj UOQgeG hggfG GfbVi GdcdGe aj TQM gPg GdebOeI GdejehfI HJhajb Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B275 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B292 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B188s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1799s
Keywords: (3GdbQGAGJ hGdJLhjOs